Interdomain flip-flop motion visualized in flavocytochrome cellobiose dehydrogenase using high-speed atomic force microscopy during catalysis. Issue 9 (3rd August 2017) - Harada, Hirofumi; Onoda, Akira; Uchihashi, Takayuki; Watanabe, Hiroki; Sunagawa, Naoki; Samejima, Masahiro; Igarashi, Kiyohiko; Hayashi, Takashi
Abstract : To visualize the dynamic domain motion of class-I CDH from Phanerochaete chrysosporium ( Pc CDH) during catalysis using high-speed atomic force microscopy, the apo-form of Pc CDH was anchored to a heme-immobilized flat gold surface that can fix the orientation of the CYT domain. Abstract : Cellobiose dehydrogenase (CDH) is a dual domain flavocytochrome, which consists of a dehydrogenase (DH) domain containing a flavin adenine dinucleotide and a cytochrome (CYT) domain containing b -type heme. To directly visualize the dynamic domain motion of class-I CDH from Phanerochaete chrysosporium ( Pc CDH) during catalysis using high-speed atomic force microscopy, the apo-form of Pc CDH was anchored to a heme-immobilized flat gold surface that can specifically fix the orientation of the CYT domain. The two domains of CDH are found to be immobile in the absence of cellobiose, whereas the addition of cellobiose triggers an interdomain flip-flop motion involving domain–domain association and dissociation. Our results indicate that dynamic motion of a dual domain enzyme during catalysis induces efficient electron transfer to an external electron acceptor.